Potential Land Extensification And Expansion In Private Oil Palm Plantations In Indonesia - Cecep Ijang Wahyudin; Rangga Rahmananda; Fachri Ibrahim Nasution; Ronal Castro; Rahayu Dwi Ningtyas; Febrianti Febrianti (Fakultas Teknologi Pertanian Unsultra, 2026)
The expansion of private oil palm plantations in Indonesia remains a critical issue due to the country’s position as the world’s largest crude palm oil (CPO) producer, with production reaching 48.23 million tonnes in 2023. This study aims to analyze the potential, constraints, and strategic opportunities for plantation extensification, particularly through the utilization of marginal lands (S2 and S3) and corporate expansion strategies such as mergers, acquisitions, and partnership schemes. A systematic literature review was conducted by synthesizing peer-reviewed journals, government statistics, and institutional reports selected based on inclusion and exclusion criteria to capture current dynamics of oil palm development in Indonesia. The findings indicate that the availability of highly suitable agricultural land (S1) is increasingly limited, encouraging companies to explore alternative strategies such as the optimization of degraded and idle lands, strengthening smallholder partnership schemes (plasma), and implementing replanting programs such as Peremajaan Sawit Rakyat (PSR). However, these opportunities are constrained by stricter environmental governance, land-use regulations, and increasing global sustainability requirements. The review further shows that S2 and S3 lands present significant biophysical limitations, including high soil acidity, poor drainage, and aluminium toxicity, which increase production costs and require advanced agronomic management. Socio-economic challenges such as land conflicts and unequal benefit distribution also continue to affect plantation expansion outcomes. This study concludes that Indonesia’s palm oil development is gradually shifting from land extensification toward productivity intensification. This transition highlights the need for stronger sustainability governance through ISPO and RSPO certification systems, improved environmental management practices, and more inclusive stakeholder engagement to ensure that plantation development remains economically viable, environmentally responsible, and socially equitable.